(untitled) (Journal of The Colloquium for Information Systems Security Education, 2024)
This paper addresses the need for incorporating global virtual team (GVT) projects into cybersecurity education curricula in an effort to develop students’ understanding of different cultures and hone their abilities to work across multiple time zones, communicate using digital communication platforms as well as improve their virtual project and time management skills. An example of a GVTs project, Virtual Business Professional, is presented in order to illustrate how collaborative online international learning (COIL) can be embedded into IT-related coursework. It is the authors’ intention to encourage instructors and administrators at institutions of higher learning to support and carry out transdisciplinary GVT projects in order to best prepare graduates for the challenges of the 21st century global workplace.